Quotation of Lou Holtz - Holtz, Lou.
Signed quotation.
Football coach. Full name: Louis Leo Holtz. Born 1937.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Football coaches